Gender equity versus job performance : an examination of the implementation of affirmative action policy at Nkonkobe Local Government Administration in the Eastern Cape Province of South Africa - Ile, Isioma Uregu (My University, 2002)
Refer to the document
Thesis (MPA.) --University of Limpopo, 2002
Keywords: Affirmative action policy; Gender; Job performance; Local government; Affirmative action programs -- South Africa -- Eastern Cape; Discrimination in employment -- South Africa -- Eastern Cape; Employees, Rating of; Equality